Genetic diversity, population structure and quality-trait associations in Blumea balsamifera revealed by EST-SSR markers - Mei Huang; Xin Li; Zhenxia Chen; Dan Wang; Kai Wang; Xuan Hu; Xiaolu Chen; Lingliang Guan; Hongrui Zhang; Yuxin Pang; Fulai Yu (PLoS ONE, 2025)
Blumea balsamifera is a widely used ancient medicinal herb in tropical and subtropical Asia. Studying the genetic diversity of B. balsamifera germplasm resources and developing molecular markers related to the content of active constituents in B. balsamifera are of great significance for breeding varieties with high active ingredient content. In this study, the contents of 6 key active constituents were determined in 51 B. balsamifera accessions. EST-SSR markers were used to study their genetic diversity. At the same time, genetic structure analysis and linkage disequilibrium analysis were performed. On this basis, association analysis between EST-SSR markers and active ingredient content was performed. Quantitative analysis revealed substantial variation in six bioactive compounds, with coefficients of variation (CV) exceeding 50% across all metabolites. This result revealed its suitability for association analysis. Genetic diversity analysis revealed a total of 102 alleles amplified from 22 pairs of primers, with effective alleles accounting for 53.52%. The average polymorphism information content was 0.488, with 9 pairs of primers exhibiting high polymorphism (PIC > 0.5), 11 pairs of primers showing moderate polymorphism (0.25 < PIC < 0.5). The proposed primers demonstrated strong effectiveness and good polymorphism. The average Nei diversity index and Shannon information index were 0.542 and 1.023, respectively, indicating a high level of genetic diversity within the population. UPGMA clustering and population structure analyses classified the 51 accessions into four distinct groups correlated with geographical origins. LD analysis indicated over 50% of marker pairs showed substantial linkage (D’ > 0.5), validating the suitability of this germplasm set for association mapping. Association analysis between quality traits and EST-SSR markers showed that, in both GLM and MLM models, Bbf137 and Bbf377 were found to be associated with 3,3’,5,7-tetrahydroxy-4’- methoxyflavanone (TMF, P < 0.05) and Blumeatin (P < 0.01) respectively. These findings lay a robust foundation for future breeding strategies and genetic enhancement of B. balsamifera.